Description of four new species of Otacilia Thorell, 1897 (Araneae: Phrurolithidae) from southern China - Shi, Songtao; Mu, Yannan; Zhang, Feng (Zootaxa, 2024)
Four new phrurolithid species of the genus Otacilia Thorell, 1897 are described from China: O. pingwu sp. nov. (♂♀; Sichuan Province), O. pugna sp. nov. (♂♀; Hunan Province), O. suining sp. nov. (♂♀; Hunan Province), and O. distorta sp. nov. (♂; Chongqing Municipality). Detailed morphological descriptions, photographs of body, copulatory organs and a distribution map of these four new species are provided.